2020
DOI: 10.1038/s41598-019-54714-w
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive global perspective on phylogenomics and evolutionary dynamics of Small ruminant morbillivirus

Abstract: A string of complete genome sequences of Small ruminant morbillivirus (SRMV) have been reported from different parts of the globe including Asia, Africa and the Middle East. Despite individual genome sequence-based analysis, there is a paucity of comparative genomic and evolutionary analysis to provide overarching and comprehensive evolutionary insights. Therefore, we first enriched the existing database of complete genome sequences of SRMVs with Pakistan-originated strains and then explored overall nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…In addition, P gene has been shown to have the highest rates of nucleotide polymorphisms, ranging from 88.6 to 99.3% [ 12 ]. Besides that, a study conducted on peste des petits ruminants virus (PPRV), another morbillivirus member, revealed that the L gene had the highest evolution rate at 9.75 × 10 − 4 site per year, while the N gene showed the lowest evolution rate at 1.1 × 10 − 3 site per year [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P gene has been shown to have the highest rates of nucleotide polymorphisms, ranging from 88.6 to 99.3% [ 12 ]. Besides that, a study conducted on peste des petits ruminants virus (PPRV), another morbillivirus member, revealed that the L gene had the highest evolution rate at 9.75 × 10 − 4 site per year, while the N gene showed the lowest evolution rate at 1.1 × 10 − 3 site per year [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feline morbillivirus (FeMV) has been speculated to cause chronic kidney disease (CKD) and it is commonly detected in urine and kidney tissue samples. Previously, conventional assays such as RT-PCR and reverse transcription loop-mediated isothermal ampli cation (RT-LAMP) have been developed targeting the L gene of FeMV [4,6,7,15,16]. However, these conventional assays were qualitative and required additional step of gel electrophoresis to visualize the PCR product.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P gene has been shown to have the highest rates of nucleotide polymorphisms, ranging from 88.6% to 99.3% [9]. Besides that, a study conducted on Peste des petits ruminant virus (PPRV), another Morbillivirus member revealed that the L gene had the highest evolution rate at 9.75 x 10 -4 site per year while the N gene showed the lowest evolution rate at 1.1 x 10 -3 site per year [15].…”
Section: Discussionmentioning
confidence: 99%
“…VLPs is a biomimetic nanostructure that can induce strong immunologic responses and high titers of neutralizing antibodies to conformational epitopes. Gardasil is the VLPs based nanovaccine accessible on the market right now, in which VLPs composed of major capsid (L1) proteins of human papillomavirus (HPV) Types 6, 11, 16, 18, 31, 33, 45, 52, and 58 [ [19] , [20] , [21] ].…”
Section: Nanovaccinesmentioning
confidence: 99%